2023
DOI: 10.1590/fst.110422
|View full text |Cite
|
Sign up to set email alerts
|

Biomanufacturing of food-grade citric acid and comprehensive utilization of its production wastewater

Abstract: Citric acid is an important and multi-functional organic acid, which is widely used in food, medicine, chemical industry and other fields. It is the largest edible organic acid in the world. Aspergillus niger is an important strain for biosynthesis of citric acid, which is mainly produced by simultaneous saccharification and fermentation with starch raw materials. The reuse of citric acid wastewater is the development direction of comprehensive utilization of citric acid wastewater. In the future, with the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The malic acid content in KFM was 0.28 mg/100 g, significantly lower than the other two fermented milk samples. Some studies have shown that yeast degrades malic acid [18]. In addition, malic acid is an intermediate product of the TCA cycle.…”
Section: The Sensory Description Physicochemical Indicators and Viabl...mentioning
confidence: 99%
“…The malic acid content in KFM was 0.28 mg/100 g, significantly lower than the other two fermented milk samples. Some studies have shown that yeast degrades malic acid [18]. In addition, malic acid is an intermediate product of the TCA cycle.…”
Section: The Sensory Description Physicochemical Indicators and Viabl...mentioning
confidence: 99%